Haplotype diversity in mitochondrial DNA hypervariable region I, II and III in a Korean ethnic group from northeast China - Zhang, YongJi; Xu, QingSong; Cui, Hong; Cui, Yan; Lin, HaiYu; Kim, KiBeom; Lee, JungBin (Forensic science international, 2005)
Sequence polymorphism of the mitochondrial DNA (mtDNA) control region, hypervariable regions HVR I, II and III, from 55 unrelated Korean ethnic group individuals from northeast China (YanBian area) were determined by PCR amplification and cycle sequencing.